The Development of Golden Triangle Program Using Head Start Approach as an Early Childhood Education Service - Lutfatulatifah Lutfatulatifah; Slamet Yulianto Wahyudi (SEAMEO CECCEP, 2022)
This research is based on the issues faced by parents and teachers during the pandemic that force the parents to accompany their children in learning from home. The common difficulty parents should encounter in accompanying their children learning from home during the Covid-19 pandemic is the lack of understanding possessed by them on their children lessons. It is probably due to the fact that previously, their children education was completely handed over only to school so that they did not involve nor comprehend the role they have in the practice of education at home. The current research is one of the attempts to reconstruct the connection among parent-teacher-child triangle. This “golden triangle” program development adopts, to some extent, the approach and principles of Head start model. It is expected that the development of this “golden triangle” program can emphasize the role of family as the first as well as main education institution for children, in addition to design the education program that encourages parents to take part in their children education. The study that had been conducted for three months using the collaborative action research method from Kemiss & McTaggar was thematically analyzed. It is found that there are three major themes; children education responsibility, “golden triangle” program implementation in early child education, and supporting factor. The task to educate early children is often handed over merely to the early childhood education institution that responsible not only on the academic side of the early children, but also their social capacity and development stimulus. The “golden triangle” program is implemented by encouraging the parents’ active participation and conducting the parent school where not only children who learn but also their parents. This program can only be implemented when there is a strong commitment and effective communication among parents, teachers, and children.